Article Review: Analysis Of Artificial Sweetness In Food And Beverages: English - Zakiyah, Wildani; Nurul Sa'adah, Cantika; Prasetyo, Fajar; Febiola Lubis, Christina; Lina Nurfadhila; Marsah Rahmawati Utami (Jurnal EduHealth, 2022)
Artificial sweeteners are substances added to food and beverages with the aim of giving a sweet taste, having no nutritional value. The types of artificial sweeteners allowed by the Minister of Health are Cyclamate, Saccharin, Aspartame and Sorbitol. The method used in this paper is a literature review study. The total journals used in this article review are 14 journals. In several studies, the levels of artificial sweeteners contained in related foods are still within the limits permitted by the government, but in some studies there are still foods whose levels of artificial sweeteners exceed the permitted limits.